2011
DOI: 10.1093/ejechocard/jer162
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of detecting early left ventricular systolic dysfunction using global area strain: a novel index derived from three-dimensional speckle-tracking echocardiography

Abstract: Global AS is a sensitive and reproducible parameter to detect early and subtle LV systolic dysfunction, showing greater feasibility than other conventional strain parameters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
47
0
7

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(55 citation statements)
references
References 19 publications
1
47
0
7
Order By: Relevance
“…Three‐dimensional STE is still very new and not yet fully validated. Table summarizes the clinical usefulness of 3D STE …”
Section: Three‐dimensional Stementioning
confidence: 99%
“…Three‐dimensional STE is still very new and not yet fully validated. Table summarizes the clinical usefulness of 3D STE …”
Section: Three‐dimensional Stementioning
confidence: 99%
“…Additionally, the midwall fiber is primarily responsible for the LV circular motion; therefore, the greatest influence on the CS and RS is the midwall fiber [39]. AS, composite motion of LS and CS, is a new concept that regional wall motion is quantified through the magnitude of deformation in an endocardial surface area [40]. Previous studies have demonstrated that the endocardial site is more sensitive to myocardial ischemia than the epicardial site [41].…”
Section: Myocardial Deformation Changes In Patients With Osamentioning
confidence: 99%
“…Для более глубокой оценки может быть полезен анализ global area (в режиме 3DT), что было продемонстрировано нами в параллельном исследова-нии, однако оценка GAS существенно увеличивала время исследования [26,27], что не позволяло рутинно использовать анализ GAS у беременных, в отличие от параметров 2DT. Следует отметить, что анализ движения кардиомиоци-тов в режиме 2DT (GLS) может служить инструментом оценки скрытой систолической дисфункции миокарда ЛЖ во время беременности, однако малый стаж АГ до беременности в сочетании с невысокими цифрами АД (2-я группа) не позволил получить достоверных различий этого параметра между 1-й и 2-й группами.…”
Section: рисунок нормальные значения Gls Gcs Grs в режиме 2dтunclassified